Peran Literasi Keuangan, Perencanaan Keuangan dan Gaya Hidup dalam Meningkatkan Pengelolaan Keuangan Karyawan SPBU Singapore - Amelia Ananda; Asnahwati Asnahwati (Universitas Methodist Indonesia, 2025)
This study aims to analyze the influence of financial literacy, financial planning, and lifestyle on the financial management of employees at the Singapore Station gas station. This study uses an associative quantitative approach. Primary data were obtained by questionnaire. The population of this study was all 50 employees of the Singapore Station Belawan gas station, all of whom were sampled using census techniques. Data analysis used multiple linear regression. Hypothesis testing consisted of t-test and f-test. The results showed that financial literacy partially influenced the financial management of employees at the Singapore Station gas station, while financial planning and lifestyle partially did not influence the financial management of employees at the Singapore Station gas station. However, simultaneously, financial literacy, financial planning, and lifestyle influenced the financial management of employees at the Singapore Station gas station. with a calculated f value of 712.733 > f table 2.81 at a significance level of 0.000 <0.05. The correlation coefficient (R) of 0.989 indicates a strong relationship between financial literacy, financial planning and lifestyle (independent variables) with financial management (dependent variable), while the Adjusted R² of 0.978 indicates that 97.8% of the proportion of financial management variations is explained by financial literacy, financial planning and lifestyle. This indicates that the regression model is very good at explaining the relationship between the independent and dependent variables with only 2.2% of the variation that cannot be explained by the model.